2017
DOI: 10.1148/radiol.2017161619
|View full text |Cite
|
Sign up to set email alerts
|

Use of Imaging to Predict Complete Response of Colorectal Liver Metastases after Chemotherapy: MR Imaging versus CT Imaging

Abstract: Purpose To compare the diagnostic performances of contrast agent-enhanced computed tomography (CT) and gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced liver magnetic resonance (MR) imaging (referred to as EOB MR imaging) in the evaluation of disappearing colorectal liver metastases (CRLMs) after chemotherapy. Materials and Methods The eight institutional review boards approved this retrospective study and waived the requirement for informed consent. On the basis of retrospective searches i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
(30 reference statements)
0
20
0
Order By: Relevance
“… 48 , 49 Gadoxetate disodium–enhanced MRI is also more accurate when compared with conventional MRI and CT for confirmation of radiologic complete response of liver metastases (“disappearing metastases”). 50 The usefulness of gadoxetate disodium for diagnosis of FNH versus HCA has recently been found to be less than previously reported, 51 and the patient population for which these diagnoses are considered are generally young healthy female patients where AKI or severe renal impairment is not anticipated. Therefore, a clinical situation where gadoxetate disodium is required to evaluate for FNH versus HCA in AKI or severe renal impairment is unlikely.…”
Section: Currently Approved Gbca For Clinical Use In Canadamentioning
confidence: 99%
“… 48 , 49 Gadoxetate disodium–enhanced MRI is also more accurate when compared with conventional MRI and CT for confirmation of radiologic complete response of liver metastases (“disappearing metastases”). 50 The usefulness of gadoxetate disodium for diagnosis of FNH versus HCA has recently been found to be less than previously reported, 51 and the patient population for which these diagnoses are considered are generally young healthy female patients where AKI or severe renal impairment is not anticipated. Therefore, a clinical situation where gadoxetate disodium is required to evaluate for FNH versus HCA in AKI or severe renal impairment is unlikely.…”
Section: Currently Approved Gbca For Clinical Use In Canadamentioning
confidence: 99%
“…After chemotherapy, no standard imaging protocol was used preoperatively, to evaluate response to chemotherapy and identify DLM although CE-CT was used as a reference or baseline in most patients. In six studies [8,9,14,15,21,23], all patients were evaluated with both CE-CT and MRI preoperatively. Types of imaging used before and after chemotherapy are presented in detail in Table 3.…”
Section: Baseline Characteristics and Treatmentsmentioning
confidence: 99%
“…According to preoperative imaging, a DLM on CE-CT was equal to a CR in 17-69% (median 51%) and 40-85% (median 78%) according to MRI. There were 3 studies specifically comparing CE-CT with EOB-MRI, and all of them showed that EOB-MRI was significantly more superior in detecting the DLM with CR [8,9,21]. In 4 studies where DLM on preoperative CE-CT were additionally evaluated with MRI and IOUS [8,9,21,23], these remaining undetectable DLM were equal to a CR in 75-94% (median 89%).…”
Section: Correlation Of Dlm To Cr and Imaging Accuraciesmentioning
confidence: 99%
See 2 more Smart Citations